Assessment of community knowledge and prevention practices of malaria in Mutale Municipality, Vhembe District - Munyai, Livhuwani (My University, 2019)
Background: Malaria is a public health issue killing more than 435 000 people in Sub Saharan Africa. In South Africa, malaria is endemic in 3 provinces namely: Limpopo, Mpumalanga and Kwazulu Natal. Limpopo Province contributes more cases than the other provinces in the country. Purpose: The purpose of the study was to assess community knowledge and prevention practices of malaria at Masisi village, in Mutale Municipality, Vhembe District. The study was conducted at Mutale municipality, Vhembe District. Methodology: A quantitative cross-sectional descriptive approach was used. Data was collected using a questionnaire with open and close ended questions. The targeted population was made up of males and females between the ages of 18 to 75. Validity and reliability have been ensured in the study and the results for reliability were 0.85. Pretesting was done in 5 household at Sanari village which is near Masisi village as they share the same characteristics. A sample of 152 participants was selected from the target population by means of systematic sampling and then select them randomly. Questionnaires were used to collect data. There after Data were analyzed using SPSS version 24.0. The analyzed data were presented in tables, graphs, and in percentages. Results: The findings revealed that majority of the participants 103(67.8%) have secondary education, and most of them, 103(67.8%) are unemployed. The study revealed that about 77% have knowledge regarding malaria transmission. About 130(85.5%) indicated that malaria is caused by a mosquito bite. About 57(38.51%) indicated that they use mosquito coils and nets in their household. Conclusion: Malaria still poses a threat to the lives of people living in malaria endemic areas. Community members at Masisi village have better insight regarding malaria transmission, causes and signs and symptoms. Although the community shows a better understanding of the prevention method they still has to put this into practice in order to eliminate malaria in the area. Health workers are doing a great job in educating the community regarding malaria related issues.
MPH
Department of Public Health
Keywords: Community; UCTD; Knowledge of malaria; Prevention practices of malaria; 614.5340968257; Insects as carrier of disease -- South Africa -- Limpopo.; Mosquitoes as carrrier of disease -- South Africa -- Limpopo.; Communicable diseases -- Prevention -- South Africa.; Malaria -- South Africa -- Limpopo.; Vector control -- South Africa -- Limpopo